As Cinco Miniaturas Brasileiras de Edmundo Villani-Côrtes: uma transcrição e edição de performance para violino e piano. - João Paulo Faria Alves de Souza (2024)
In this dissertation, we present a transcription for violin and piano of the suite “Cinco Miniaturas Brasileiras” by Edmundo Villani-Côrtes, as well as a Performance Edition of the same work. Drawing from my experience as a violin professor at the institution State Conservatory of Music Haidée França Americano, one of the twelve music conservatories in the state of Minas Gerais, Brazil, I noticed a lack of Brazilian compositions specifically tailored for intermediate-level instrumental practice within the curriculum of this institution. To address this issue, we selected a piece by a fellow Brazilian composer of national significance for the development of this research. In this study, we delve into who Villani-Côrtes is and explore his contribution to Brazilian music, particularly in the concert music. Additionally, we introduce the institution State Conservatory of Music, highlighting the characteristics that guide musical and instrumental education there. We analyzed the technical content present in the curriculum of the 1st and 2nd years of the Technical Violin Course at the institution State Conservatory of Music Haidée França Americano, in order to collect the key violinistic techniques taught and to assist in our transcription. Finally, we propose a transcription in a Performance Edition, discussing the techniques to be employed and the rationale behind our suggested choices, with the aim of applying this repertoire to the technical and musical development of intermediate-level students.